Prospective memory: Effects of divided attention on spontaneous retrieval. - Harrison, Tyler; Mullet, Hillary; Whiffen, Katie; Ousterhout, Hunter; Einstein, Gilles (Memory & Cognition, 2014)
We examined the effects of divided attention on the spontaneous retrieval of a prospective memory intention. Participants performed an ongoing lexical decision task with an embedded prospective memory demand, and also performed a divided-attention task during some segments of lexical decision trials. In all experiments, monitoring was highly discouraged, and we observed no evidence that participants engaged monitoring processes. In Experiment 1, performing a moderately demanding divided-attention task (a digit detection task) did not affect prospective memory performance. In Experiment 2, performing a more challenging divided-attention task (random number generation) impaired prospective memory. Experiment 3 showed that this impairment was eliminated when the prospective memory cue was perceptually salient. Taken together, the results indicate that spontaneous retrieval is not automatic and that challenging divided-attention tasks interfere with spontaneous retrieval and not with the execution of a retrieved intention.